Rice husk : carbon dioxide reducer - Azmi, Ariff; Mohd Zarak, Muhamad Firdaus; Che Teh, Ahmad Azamuddin; Mohd Adnan, Raudah; Mohd Ghazali, Jamilah; Abu Bakar Sidik, Dilaeleyana (Penerbit UTHM, 2020)
Carbon dioxide can bring a major effect to the environment and lead us to the global warming and Green House effect. Besides that, it been listed as the major waste in the world that cannot easily be disposed. Due to these problems, many scientists recently investigate about how to overcome this issue. One of the uncostly and easy ways is using rice husk. It has been known that rice husk has the same characteristic with activated carbon which can adsorb carbon dioxide. This rice husk adsorbs carbon dioxide by trapping it into their pores. The main objective of this experiment is to study the tendency of rice husk as activated carbon to adsorb carbon dioxide. To generate the activated carbon behaviour, rice husk must be reacted with potassium hydroxide solution (KOH). The mixture of rice husk with Potassium hydroxide solution is dry by using oven. The dried rice husk is put into the Fourier-transformer Infrared (FTIR) to obtain the exact result to determine the compound that has the activated carbon behaviour. The range of the test is between 4000 to 650. The Fourier-transformer Infrared (FTIR) shows that activated carbon compound that has the least amount of peak is the best because it represents least amount of organic compound in that rice husk. So that the tendency to adsorb carbon dioxide is high.